Controlled Switched Reluctance Motors with Energy Capacitor - Vasyl Tkachuk; Lidiya Kasha; Ihor Bilyakovskyy; Mykhailo Khai (Energy Engineering and Control Systems)
One of the most simple in terms of construction, the most practically feasible and reliable motors is a switched motor with salient-pole stator, concentrated coils and its winding and toothed passive rotor. Such motor is simpler, cheaper and more practically technical than asynchronous motor and by control characteristics does not concede to DC motors. The basic electrical scheme of a commutator with capacity buffers of energy of switched reluctance motor and circumscribed, the new phase-width mode by regulating frequency of reversion of such drives is offered. The width-phase speed control, where there is a functional relationship, is described in this paper.